UMA MÁQUINA DE FAZER O MESMO: : O ESTEREÓTIPO E A DISPUTA PELOS SENTIDOS EM DISCURSOS SOBRE O REGGAETON NA GRANDE MÍDIA BRASILEIRA - Bastos de Souza, Nathan (Cadernos de Linguagem e Sociedade, 2020)
In this paper we studied the discourses about the reggaeton in newspapers of great virtual circulation in Brazil. The theoretical basis is the concept of stereotype developed by Amossy and Pierrot, Gamarnik and Burke and the analysis methodology is based on the indicative paradigm by Ginzburg. We selected some texts that circulated during 2017 in the newspapers Folha de São de Paulo, O Globo and El País. Our analysis allows us to affirm that reggaeton and its singers are stereotyped because there is a crystallized and previous image that links Latin music to sexuality and it induces to devalue the songs considered of low quality because they are the result of popular culture.